Practical Counseling and Communication Strategies: Tobacco Cessation - Laura Romito; Lorinda Coan; Arden Christen (Association of American Medical Colleges, 2013)
Abstract Tobacco use is a primary cause of preventable morbidity and mortality worldwide. Therefore, it is critical that health care providers address the issue of tobacco use and dependence with their patients. The purpose of this module is to explain and demonstrate the application of communication techniques for patient tobacco cessation counseling. This presentation contains three formative learning activities and several video clips demonstrating communication techniques involved in tobacco cessation counseling interventions. It also includes a slide script, reference list, and instructor's guide, as well as a sample 10-item assessment based on the content of the module. The content of this module is significant for learners about to enter the clinical setting, or already involved in patient care because they can readily apply the material to a clinical encounter. Health professions students and practitioners are often reticent to discuss tobacco use because they lack the time and skills to do so or are afraid of offending patients. After completion of the module, the student should be better prepared to communicate with patients in a more effective manner when discussing tobacco use and dependence and attempting to encourage a behavior change (tobacco cessation). The module presents evidence-based behavioral and communication strategies and techniques which have been shown to be effective in tobacco counseling. As such, it is anticipated that they may be more likely to engage their tobacco-using patients in education and cessation counseling.